Der p 1 gene sequence polymorphism in house dust mite Dermatophagoides pteronyssinus - Aryani Adji; NURDJANNAH J. NIODE; VENTJE V. MEMAH; JIMMY POSANGI; GRETA J. P. WAHONGAN; TRINA E. TALLEI (Society for Indonesian Biodiversity, 2021)
Abstract. Adji A, Niode NJ, Memah VV, Posangi J, Wahongan GJP, Tallei TE. 2021. Der p 1 gene sequence polymorphism in house dust mite Dermatophagoides pteronyssinus. Biodiversitas 22: 72-78.  Gene polymorphisms in Dermatophagoides pteronyssinus (DP) mite can affect the immune response that plays a role in atopic disease. This study aimed to determine the polymorphisms of Der p 1 gene from DP. House dust containing DP was used as a source of DNA containing the Der p 1 gene. The gene was amplified using specific primers DP Der 1 P 108F and DP Der 1 P 1509R. The amplified fragments were cloned using the Toyobo pTA2 vector and sorted then compared with the Gene Bank database. The result shows that there are 8 polymorphism sites in the Der p 1 gene positioned at 190 (GR), 463 (CT), 645 (AR), 751 (CY, CT), 787 (CG), 827 (TA; TW), and 1084 (CG). In the Der p 1 gene, there are 5 silent mutations and 3 nonsynonymous substitutions, resulting in amino acid polymorphisms as follows: Histidine H146 to Tyrosine Y146, Alanine A220 to Valine V220 and amino acid X220, and Tyrosine T232 to Serine S232. Polymorphisms in these amino acids lead to a polarity change, from polar to polar and non-polar to non-polar. These dynamics in polarity does not change the structure or function of the allergen protein. So that they can be used for vaccine design strategies.